2013
DOI: 10.1063/1.4801534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal organic chemical vapour deposition growth conditions on vibrational and luminescent properties of ZnO nanorods

Abstract: A detailed optical characterization by means of micro Raman and cathodoluminescence spectroscopy of catalyst-free ZnO nanorods grown by atmospheric-metal organic chemical vapour deposition has been carried out. This characterization has allowed correlating the growth conditions, in particular the precursors partial-pressures and growth time, with the optical properties of nanorods. It has been shown that a high Zn supersaturation can favor the incorporation of nonradiative recombination centers, which can tent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the PL spectra of the ZnO NCs, a narrow near-band edge emission (NBE) around 380 nm and a broad band deep-level emission (DLE) between 450 nm to 700 nm were generally observed [5][6][7][8]27]. Figure 3 shows the spectra normalized to the absorbance at λex = 290 nm.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the PL spectra of the ZnO NCs, a narrow near-band edge emission (NBE) around 380 nm and a broad band deep-level emission (DLE) between 450 nm to 700 nm were generally observed [5][6][7][8]27]. Figure 3 shows the spectra normalized to the absorbance at λex = 290 nm.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
“…The stronger suppression of the NBE band compared to the DLE band most likely indicated that RE ions acted as non-radiative defects, the origin of which was different from the radiative defects responsible for the DLE band. In the PL spectra of the ZnO NCs, a narrow near-band edge emission (NBE) around 380 nm and a broad band deep-level emission (DLE) between 450 nm to 700 nm were generally observed [5][6][7][8]27]. Figure 3 shows the spectra normalized to the absorbance at λ ex = 290 nm.…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
See 1 more Smart Citation
“…There are many synthesized techniques that have been introduced for the growth of a set of ZnO nanorods on the large domain of substrates [15]. These techniques contain radiofrequency magnetron sputtering [16], metallic organic chemical vapor deposition (MOCVD) [17], chemical vapor deposition (CVD) [18], pulsed laser deposition [19], vapor phase transport [20], spray pyrolysis [21] and electrochemical deposition [22]. During these techniques mention above, the chemical bath deposition (CBD) method is a low-temperature technique, and possibly the lowest cost method for growing ZnO nanorods not need the high production yield [23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique optical, semiconductor, and optical properties, ZnO thin films have been extensively studied for various applications. Several methods such as chemical bath deposition, MOCVD, melt growth, ion implementation, DC reactive magnetron cosputtering, and hydrothermal and simple chemical pyrolysis have been used to synthesize ZnO thin films [7][8][9][10][11][12][13]. Of late, ZnO thin films are being fabricated by codoping for enhancing the efficiency of ZnO film in optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%